Persepsi Masyarakat Desa Talunblandong Kabupaten Mojokerto pada Dakwah Bil Lisan Kiai Falaqul Alam - Luluk Kamila Iftitakhurrohmah; Clara Sinta Pratiwi (Jurnal Manajemen dan Pendidikan Agama Islam, 2025)
This study is motivated by the ongoing practice of oral dakwah methods amidst the rapid development of technology and the growing variety of dakwah media. Although digital dakwah is increasingly widespread, direct oral preaching still holds a special place in the hearts of the community. The focus of this research is the perception of the Talunblandong Village community towards the oral dakwah delivered by Kiai Falaqul Alam, as well as how they receive and interpret it. This study also examines the impact of this dakwah on the social and religious life of the community. The research employs a qualitative approach with Edmund Husserl’s phenomenological method, emphasizing individuals’ subjective experiences. Data were collected through in-depth interviews, observation, and documentation involving community members who attend Kiai Falaqul Alam’s dakwah. Data analysis was conducted using Descriptive Phenomenological Research (PFD), including unit of meaning description, psychological description, structural description, and thematic synthesis. This process aims to uncover the deepest meaning of the community’s experience of the dakwah they receive. The results show that Kiai Falaqul Alam is perceived as a wise preacher with an easy-to-understand and socially relevant preaching style. The community responds enthusiastically because the content of the sermons meets their spiritual needs and everyday life. The dakwah has positively impacted the community by increasing religious awareness, changing behaviors, and fostering a spirit of togetherness. This indicates that oral dakwah remains an effective method for conveying Islamic values in a touching and lasting way.